Metabolic aging and cutaneous markers of metabolic syndrome: a narrative review - Theressia Handayani; I Made Jawi (Explorer Front, 2025)
Metabolic syndrome (MetS) is a constellation of metabolic abnormalities—including central obesity, dyslipidemia, hypertension, and impaired glucose regulation—that considerably increases cardiometabolic risk. Recent evidence emphasizes that MetS significantly influences the skin, which serves as a visible indicator of underlying metabolic dysfunction. The emerging concept of metabolic aging describes the acceleration of biological aging driven by chronic metabolic stress through mechanisms such as inflammaging, oxidative stress, mitochondrial dysfunction, microvascular injury, and the accumulation of advanced glycation end products (AGEs). Cutaneous signs associated with insulin resistance—including acanthosis nigricans, skin tags, acne in PCOS, hidradenitis suppurativa, and early-onset androgenetic alopecia (AGA)—are increasingly recognized as reliable clinical markers of metabolic dysregulation. Early-onset AGA has a strong epidemiological association with insulin resistance, dyslipidemia, and increased cardiometabolic risk. Understanding these links is essential for dermatologists and aesthetic practitioners, as metabolic dysfunction affects wound healing, treatment response, and procedural safety. This narrative review aims to summarize current evidence on the relationship between metabolic syndrome, metabolic aging, and cutaneous manifestations, with particular emphasis on clinically observable dermatologic markers of insulin resistance and their implications for dermatology and aesthetic practice.